Polyelectrolyte-activated carbon composite electrodes for inverted membrane capacitive deionization (iMCDI) - Fritz, Pina A. (2021)
A new way of desalination using capacitive deionization (CDI) technology is by inverting the potential profile (inverted capacitive deionization iCDI). This means ions adsorb to the electrodes at 0 V and desorb when biasing the electrodes to larger potential differences. Previously, this operation was achieved by preparing electrode materials with anionic and cationic surface charges. Here we show, as a novelty, that an inverted CDI operation is also possible with conventional activated carbon electrodes when used in combination with ion exchange membranes (inverted membrane capacitive deionization iMCDI). Further we show that, the salt separation could be increased to 5.2 mg/g using 0 V for ion loading and −1.5 V for regeneration of polyelectrolyte-activated carbon composite electrodes. These are made with a water soluble styrene butadiene rubber binder and positively (poly(diallyldimethyl-ammoniumchloride)) and negatively charged (polystyrene sulfonate) polyelectrolytes and used in combination with ion exchange membranes. This leads to increased separation performance, and exergy efficiency, whereas cumulative exergy loss values remain low, indicating promising resource use efficiencies, competitive with conventional membrane capacitive deionization (MCDI).